Ethical conflicts during the process of deciding about ICU admission: an empirically driven ethical analysis. Issue 12 (5th January 2021) - Svantesson, Mia; Griffiths, Frances; White, Catherine; Bassford, Chris; Slowther, AnneMarie
Abstract : Background: Besides balancing burdens and benefits of intensive care, ethical conflicts in the process of decision-making should also be recognised. This calls for an ethical analysis relevant to clinicians. The aim was to analyse ethically difficult situations in the process of deciding whether a patient is admitted to intensive care unit (ICU). Methods: Analysis using the 'Dilemma method' and 'wide reflective equilibrium', on ethnographic data of 45 patient cases and 96 stakeholder interviews in six UK hospitals. Ethical analysis: Four moral questions and associated value conflicts were identified. (1) Who should have the right to decide whether a patient needs to be reviewed? Conflicting perspectives on safety/security. (2) Does the benefit to the patient of getting the decision right justify the cost to the patient of a delay in making the decision? Preventing longer-term suffering and understanding patient's values conflicted with preventing short-term suffering and provision of security. (3) To what extent should the intensivist gain others' input? Professional independence versus a holistic approach to decision-making. (4) Should the intensivist have an ongoing duty of care to patients not admitted to ICU? Short-term versus longer-term duty to protect patient safety. Safety and security (experienced in a holistic sense of physical and emotional security for patients) were key values at stake in the ethical conflicts identified. The life-threatening nature of the situation meant that the principle of autonomy was overshadowed by the duty to protect patients from harm. The need to fairly balance obligations to the referred patient and to other patients was also recognised. Conclusion: Proactive decision-making including advance care planning and escalation of treatment decisions may support the inclusion of patient autonomy. However, our analysis invites binary choices, which may not sufficiently reflect reality. This calls for a complementary relational ethics analysis.